Effects of Using a Combination of Real and Virtual Labs Based on the 5E Learning Cycle Model on Electrical Student Learning Outcomes - Ben Ouahi , Mhamed; Zghida , Noureddine; Omari, Slimane; Belhadj , Karim; Chakir, El Mahjoub; Tan, Emerita M (Universitas Negeri Semarang, 2024)
The 5E instructional model is an inquiry-based learning approach. This model is an effective approach to improving student learning outcomes. It is currently implemented using virtual experiments or a combination of real and virtual experiments. This research aims to investigate the effects of using a real laboratory (RL), a virtual laboratory (VL), and a combination of RL and VL based on the 5E learning cycle model on student learning outcomes in the subject of electricity. A quasi-experimental design involving pre-test and post-test comparisons between groups was employed in this research. The research sample consisted of 166 first-year students from a rural middle school. Students were divided by reasoned choice into three groups. The first group (RL) included 58 students (using real laboratory activities), the second group (VL) included 56 students (using virtual laboratory activities), and the third group (RL+VL) included 52 students (using both real and virtual laboratory activities). The research was conducted during the second semester of the 2022 school year. Data were analyzed using a paired-sample t-test, one-way ANOVA, and N-Gain. The results reveal that the combined use of real and virtual lab activities results in a more substantial improvement in student learning outcomes than using real or virtual labs alone.